Historical synthesis of the coca’s biosocial studies and nutrition in Peru, 1948-1994 - Ayala Pío, Salomón (2019)
The objective of this paper is to offer a historical perspective about the scientific investigations respect to the chewing of coca leaves and food ingestion of the Andean population during the second half of the twentieth century. The habit of cocaism was considered one of the most important problems of Public Health in Peru during the 40s, period when the academic debate of the association of deficient food and cocaism was discussed. Years later, epidemiological studies supported this paradigm; however, since the 70s, anthropological reports questioned that claim and defended the social use of coca chewing. During the 80s the pharmacological effects of coca and cocaine were demonstrated in reduction of food consumption in experimental animals, which supported the old Gutierrez-Noriega´s hypothesis.